Integrasi Kearifan Lokal Batik Gedhok dalam Pembelajaran Tematik di Sekolah Dasar - Miskiyyah, Sylvia Zakiyyatul; Yulia, Nurul Mahruzah (CV. Kurnia Grup, 2025)
Batik Gedhog, as a cultural heritage typical of Tuban Regency, has philosophical and aesthetic values that can be integrated into various subjects in thematic learning. Through contextual learning based on local culture, students not only understand academic materials but also foster an attitude of love for culture, positive character, and strengthening the Pancasila Student Profile. Literature analysis shows that the integration of local wisdom in thematic learning has the potential to increase relevance, attractiveness, and meaningfulness in the learning process. However, implementation in the field still faces challenges, such as limited teaching resources and teacher training. Therefore, collaboration between schools, government, and the community is needed to develop learning based on local culture in a sustainable manner.